2018
DOI: 10.1111/btp.12555
|View full text |Cite
|
Sign up to set email alerts
|

Host plant distributions and climate interact to affect the predicted geographic distribution of a Neotropical termite

Abstract: Species distribution models (SDMs) have been widely used in the scientific literature. The majority of SDMs use climate data or other abiotic variables to forecast the potential distribution of a species in geographic space. Biotic interactions can affect the predicted spatial distribution of a species in many ways across multiple spatial scales, and incorporating these predictors in an SDM is a current topic in the scientific literature. Constrictotermes cyphergaster is a widely distributed termite in the Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The geographic distribution of a species depends on the relationships among the biotic, abiotic, and historical factors, and climate plays a fundamental role in this distribution (Peterson et al 2011;Cunha et al 2018). According to the current map of ecological niche model, this species presented broad climatic suitability area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographic distribution of a species depends on the relationships among the biotic, abiotic, and historical factors, and climate plays a fundamental role in this distribution (Peterson et al 2011;Cunha et al 2018). According to the current map of ecological niche model, this species presented broad climatic suitability area.…”
Section: Discussionmentioning
confidence: 99%
“…Another troublesome factor is the state of land use in the new potential areas for D. alata (in future scenarios). The ecological niche model used here produces conservative results because other variables such as land use were not considered (Hannah et al 2002;Cunha et al 2018). This is especially important considering that the Cerrado has experienced intense occupation and land use conversion, mainly for grazing and agriculture (e.g., soybeans and sugar cane) (Sawyer 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Asclepias availability as well as climatic variables, including minimum temperature of the coldest month, as key for structuring the western monarch breeding grounds. These findings add to the increasing body of evidence suggesting that biotic interactions may govern species distributions as strongly as environmental conditions (Dilts et al n.d., Araújo and Luoto 2007, Preston et al 2008, Schweiger et al 2008, de Araújo et al 2014, Fraterrigo et al 2014, Lemoine 2015, da Cunha et al 2018).…”
Section: Who Identifiedmentioning
confidence: 99%
“…This so-called "climate envelope approach" are based on the Eltonian noise hypothesis, which posits that biotic interactions may be a major driver of abundance at smaller spatial resolutions, but at larger and coarser spatial resolutions the effects of biotic interactions may average out, leaving abiotic factors as the principal drivers (Guisan and Thuiller 2005, Soberon and Nakamura 2009, Elith and Leathwick 2009. Yet recent modelling studies have identified biotic factors as important drivers of species distributions (Dilts et al n.d., Araújo and Luoto 2007, Preston et al 2008, Schweiger et al 2008, de Araújo et al 2014, Fraterrigo et al 2014, Lemoine 2015, da Cunha et al 2018 and SDMs predictions for species response to climate change have yielded contrasting results based upon whether or not biotic factors are included (Preston et al 2008, Schweiger et al 2008, Lemoine 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called "climate envelope approach" is based on the Eltonian noise hypothesis, which posits that biotic interactions may be a major driver of abundance at smaller spatial resolutions, but at larger and coarser spatial resolutions, the effects of biotic interactions may average out, leaving abiotic factors as the principal drivers (Guisan and Thuiller 2005, Elith and Leathwick 2009, Soberon and Nakamura 2009, Fraterrigo et al 2014). Yet, recent modeling studies have identified biotic factors as important drivers of species distributions (i.e., Ara újo and Luoto 2007, Preston et al 2008, Schweiger et al 2008, de Ara újo et al 2014, Lemoine 2015, da Cunha et al 2018, Dilts et al 2019; and SDMs' predictions for species response to climate change have yielded contrasting results based upon the inclusions of biotic factors (Preston et al 2008, Schweiger et al 2008, Lemoine 2015. Accordingly, climate envelope modeling may accurately define the potential niche of a species, but the realized niche, defined in part by species interactions, may differ substantially.…”
Section: Introductionmentioning
confidence: 99%